Hypertrophy of the mandibular coronoid process and structural alterations of the condyles associated with limited buccal opening: case report - Mazzetto,Marcelo Oliveira (2007)
This paper reports the case of a patient who presented limited buccal opening, though, without apparent symptomatology. The patient was partially toothless and exodontia of the remaining teeth was indicated. Clinical examination and clinical interview were performed as well as panoramic radiograph, transcranial radiograph of the temporomandibular joints (TMJ) and, later, computed tomography (CT), emphasizing the importance of complementary exams in the diagnostic phase. Analysis of the CT scan confirmed the structural alteration in the condylar and coronoid processes of the jaw, explaining the limited buccal opening. The remaining teeth were extracted and complete upper and lower dentures were fabricated, reestablishing the occlusal relationship and the patient's stomatognathic functions. Surgical treatment of the coronoid process was discarded.